Radiocarbon Dates Associated to Neolithic Contexts (Ca. 5900 – 2000 Cal BC) from the Northwestern Mediterranean Arch to the High Rhine Area. (17th March 2021) - Martínez-Grau, Héctor; Morell-Rovira, Berta; Antolín, Ferran
This paper presents a compilation of radiocarbon dates associated with the process of arrival, development and consolidation of the first farming communities that settled between the north-western Mediterranean Arch and the High Rhine area approximately between 5900 and 2000 cal BC covering a large geographical area previously out of the main focus of 14 C data compilations. The database includes dates from scientific publications and it incorporates several fields for evaluating the quality and the reliability of the available samples. It overall provides 3617 radiocarbon dates that allow the scientific community to build chronological models that can be combined with other proxies such as spatial location, type of sample or chronocultural phase.